Effectiveness of local economic development (LED) policies in the improvement of revenue generation and employment condition a case study of Antipolo City, Philippines - Adhikari, Ramesh (2012)
Key Words: Local economic development, Competitive, Employment, Revenue and Spatial strategy.The study investigates the effectiveness of local economic development policies in improving the revenue generation by the city government and employment condition in Antipolo City. It examined the roles of city government, NGOs and private sector in local economic development, assessed the competitiveness of city economy, and examined the linkages local economic development plan and spatial plan of the city. The City Government of Antipolo, non-government and private sector organizations performed their roles well to enhance the local economy. City government has contributed in the city economy by involving in plan preparation and assisting city government in service delivery; and business sector has contributed in the city economy with increased internal revenue by city government and employment in the city during the period of 2000-2010.The City of Antipolo attained a competitiveness index of six out of ten, which is categorized as being competitive but needs some improvement. Major LED policies employed by city government since 2000 such as the revenue code, tax incentive code, streamlining the business registration procedure, and ordinances that require mandatory provision of employment to local people in local businesses and construction activities. among others have contributed to the higher level of revenue generation by the city government and employment of the city during the period of 2000-2010. The LED plan and the land use plan of City Government of Antipolo are aligned. The six growth centers of the city have their distinct economic roles, which are being aligned with spatial strategy of the city. Nonetheless, the economic opportunities are not equitably distributed among barangay. The recommendations are geared towards incentive-based economic policies that are aimed to equalize the economic opportunities among the barangay in the City of Antipolo.